Sustainable Agriculture Volume 2 2011
DOI: 10.1007/978-94-007-0394-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Fertiliser Trees for Sustainable Food Security in the Maize-Based Production Systems of East and Southern Africa

Abstract: -The negative effects of soil fertility depletion on food security, especially among smallholder farmers in Africa, is of economic importance, and may be worsened by climate change and rising global fertiliser prices. Substantial efforts and investment have gone into development of alternative soil fertility management options. These include vigorous research and development of N-fixing plants or "fertiliser trees", that has been on-going in the last two decades in East and Southern Africa. In this paper, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Hobbs and Govaerts, (2010) observed that CA results in improved soil physical and biological health, better nutrient cycling and crop growth as well as increasing water infiltration (Ranging from 45 to 87% increase in infiltration rate with CA compared to conventional practices) and soil penetration by roots, which allows crops to better adapt to lower rainfall and make better use of water. Akinnifesi et al, (2011) reported that some fertilizer trees can add up to 60 kg N/ha/yr, reduce the need for mineral fertilizers by 75% and substantially increase crop yield. In some conditions (East and Southern Africa), the use of fertilizer trees can double maize yield and, thus, enhance profit and net returns Akinnifesi et al, (2011).…”
Section: Concerns and Trade-offs Of Implementing Camentioning
confidence: 99%
See 1 more Smart Citation
“…Hobbs and Govaerts, (2010) observed that CA results in improved soil physical and biological health, better nutrient cycling and crop growth as well as increasing water infiltration (Ranging from 45 to 87% increase in infiltration rate with CA compared to conventional practices) and soil penetration by roots, which allows crops to better adapt to lower rainfall and make better use of water. Akinnifesi et al, (2011) reported that some fertilizer trees can add up to 60 kg N/ha/yr, reduce the need for mineral fertilizers by 75% and substantially increase crop yield. In some conditions (East and Southern Africa), the use of fertilizer trees can double maize yield and, thus, enhance profit and net returns Akinnifesi et al, (2011).…”
Section: Concerns and Trade-offs Of Implementing Camentioning
confidence: 99%
“…Akinnifesi et al, (2011) reported that some fertilizer trees can add up to 60 kg N/ha/yr, reduce the need for mineral fertilizers by 75% and substantially increase crop yield. In some conditions (East and Southern Africa), the use of fertilizer trees can double maize yield and, thus, enhance profit and net returns Akinnifesi et al, (2011).…”
Section: Concerns and Trade-offs Of Implementing Camentioning
confidence: 99%
“…There are numerous proven options of enhancing the WUE, and their adoption must be promoted through soil governance. Improving soil fertility by establishing fertilizer trees [112] can also improve WUE in drought-prone agroecosystems.…”
Section: Managing Water For Alleviating Drought Stressmentioning
confidence: 99%
“…Fertilizer trees, grown as agroforestry systems, can restore soil fertility and productivity. Akinnifesi et al [112] reported that some fertilizer trees can add up to 60 kg N/ha/yr, reduce the need for mineral fertilizers by 75% and substantially increase crop yield. In some conditions (East and Southern Africa), the use of fertilizer trees can double maize yield and, thus, enhance profit and net returns [112].…”
Section: Sustainable Managementmentioning
confidence: 99%
See 1 more Smart Citation